Direct Shear Strength on the São Francisco River Bank, Northeastern Brazil, With or Without Roots of Different Native Species - Rocha, Igor Pinheiro da; Holanda, Francisco Sandro Rodrigues; Rolim, Mario Monteiro; Pedrotti, Alceu; Moura, Marks Melo; Santos, Luiz Diego Vidal (Journal of Agricultural Studies, 2021)
Several plant species have been studied as reinforcement elements against landslides at slopes, either to protect against the splash effect offered by shoots or anchoring the soil by the root system. The objective of this work was to investigate the influence of roots from shrub species over the soil mechanical attributes such as cohesion and angle of internal friction at the São Francisco riverbank, northeastern Brazil. A trench was excavated under the treetop of every shrubby individual, sampling blocks at 0-0.25, 0.25-0.50, 0.50-0.75, and 0.75-1.00 m depths. The moisture contents, particle size, liquidity limits, plasticity and actual specific mass of the samples were determined. The soil physical and mechanical attributes such as initial and final specific weight, initial and final void content, initial and final degree of saturation, shear resistance peaks, cohesion, and internal friction angle were identified through direct, elementary, consolidated, and undrained tests. In the samples with Solanum paniculatum, Mimosa pigra species, the highest values for cohesion were registered for the samples with roots. Sesbania virgata presented the greatest variation in cohesion and internal friction angle among samples with and without roots. The position and root status influenced the results of the direct shear tests.